Enhancing perioperative landmark detection during sacroiliac joint fusion in patients suffering from low back pain. Issue 1 (1st January 2021) - Schippers, Bas; Hekman, Edsko; van Helden, Sven; Boomsma, Martijn; van Osch, Jochen; Nijveldt, Robert
Abstract: Over the past decade, minimally invasive sacroiliac joint (SIJ) fusion has become an effective treatment for patients suffering from low back pain (LBP) originating from the SIJ. Perioperative C-arm fluoroscopy-assisted surgical navigation during SIJ fusion remains challenging due to the lack of 3D spatial information. This study developed and assessed a 3D CT/2D fluoroscopy integration approach based on digitally reconstructed radiographs (DRRs) obtained from pre-operative CT scans. Development of this approach proved feasible and landmarks were successfully translated, in retrospect, to perioperatively acquired fluoroscopies. Further expansion of and research into the proposed approach to increase perioperative navigation is indicated and additional validation should be performed.